Effectiveness of Imagery Relaxation Therapy on Blood Pressure Levels Among Elderly Patients with Hypertension - Aulia Pradana Satya Kiran; Suri Salmiyati; Zubaida Rohmawati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Hypertension remains a leading contributor to cardiovascular morbidity among older adults, particularly in rural populations with limited access to comprehensive management strategies. This study examined the effectiveness of imagery relaxation therapy on blood pressure levels among elderly patients with hypertension using a quantitative pre-experimental one-group pretest–posttest design. Forty-nine participants aged 60–70 years underwent a structured 10–15 minute imagery relaxation session, and blood pressure was measured immediately before and after the intervention. Paired sample t-tests revealed a significant reduction in systolic blood pressure (mean difference = 17.43 mmHg; 95% CI: 13.76–21.10; p < 0.001) and diastolic blood pressure (mean difference = 7.71 mmHg; 95% CI: 6.56–8.87; p < 0.001). Additionally, 69.4% of participants demonstrated improvement in blood pressure category, with no cases of deterioration observed. These findings indicate that imagery relaxation therapy yields clinically meaningful hemodynamic benefits and may serve as an effective adjunctive intervention within community-based hypertension management for elderly populations.